2022
DOI: 10.1002/anie.202117760
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I)‐Catalyzed Asymmetric Synthesis of P‐Chiral Aminophosphinites

Abstract: Herein, a copper(I)-catalyzed reaction of diarylphosphines and O-benzoyl hydroxylamines is developed. In the cases of symmetrical diarylphosphines, a series of aminophosphinites is prepared in high yields.In the cases of unsymmetrical diarylphosphines, an array of P-chiral aminophosphinites is synthesized in high yields with high enantioselectivity by using a copper(I)-(R,R P )-Ph-FOXAP complex as a chiral catalyst. Based on several control experiments and 31 P NMR studies, a two-electron redox mechanism invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…We hypothesized that any metal can mediate rapid P-inversion, which is supported by experimental data for complexes of Ti, Zr, Hf, Nb, W, Mo, Re, Fe, Ru, Ni, Pd, Pt, and Ir, with d 0 , d 2 , d 4 , d 6 , and d 8 configurations . NMR and computational studies of chiral Cu­(I) phosphido complexes , and the recent development of highly enantioselective Cu­(Taniaphos)-catalyzed asymmetric P-alkylation were also consistent with this idea, but inversion barriers in d 10 metal–phosphido complexes had not been measured, and an unusually high computed barrier of 25 kcal/mol was reported for the model complex CpZnPH 2 . Even if P-inversion in Cu–phosphido catalytic intermediates was slower than P-alkylation, enantioselection could occur by the black route in Scheme .…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…We hypothesized that any metal can mediate rapid P-inversion, which is supported by experimental data for complexes of Ti, Zr, Hf, Nb, W, Mo, Re, Fe, Ru, Ni, Pd, Pt, and Ir, with d 0 , d 2 , d 4 , d 6 , and d 8 configurations . NMR and computational studies of chiral Cu­(I) phosphido complexes , and the recent development of highly enantioselective Cu­(Taniaphos)-catalyzed asymmetric P-alkylation were also consistent with this idea, but inversion barriers in d 10 metal–phosphido complexes had not been measured, and an unusually high computed barrier of 25 kcal/mol was reported for the model complex CpZnPH 2 . Even if P-inversion in Cu–phosphido catalytic intermediates was slower than P-alkylation, enantioselection could occur by the black route in Scheme .…”
Section: Introductionmentioning
confidence: 62%
“…Although enantioselectivity was low, these results demonstrated that copper-catalyzed asymmetric P-alkylation was possible . Later, Yin and coworkers showed that a related Cu­(Taniaphos) catalyst was highly selective …”
Section: Resultsmentioning
confidence: 99%
“…Organophosphorous partners bearing P−H bonds with a wide range of acidities (p K a 9.0 to 22.4) [13] can be activated with transition metal catalyts [14] . For secondary phosphines, coordination followed by deprotonation results in a metal‐phosphido complex [9a,c,e–k,15] with high nucleophilicity, and recent studies have revealed impressive versatility of catalytically generated Cu‐phosphido complexes [9e,g–h,15a‐e,k‐m] . Glueck elucidated mechanistic and structural details, [15d,e] while both Glueck and Yin demonstrated catalytic transformations using Cu‐phosphidos (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…By employing O-benzoyl hydroxylamines 81 as electrophilic reaction partners, and the complex of Cu(CH 3 CN) 4 PF 6 and (R,R P )-Ph-FOXAP L14 as the catalyst, various P-chiral aminophosphinites 82 were furnished in high yields with high enantioselectivity (Scheme 24). [51] It is noteworthy that alkylarylphosphines were unsatisfactory substrates with only trace desired products obtained. This is a limitation of this strategy, so it should be overcome in the future.…”
Section: Scheme 19 Pincer Pd-catalyzed Asymmetric Alkylationmentioning
confidence: 99%